A Transformer Partial Discharge Measurement System Based on Fluorescent Fiber - Fan Liu; Ju Tang; Jiabin Zhou; Xiaoxing Zhang (Energies, 2012)
Based on the physical phenomena of optical effects produced by the partial discharge (PD) and on the characteristics of fluorescent fiber sensing of weak fluorescent signals, a PD measurement system using a fluorescent fiber sensor was designed. The main parameters of the sensing system were calculated, an experimental testing platform for PD simulation in the lab was established, and PD signals were then detected through ultra-high frequency (UHF) and optical methods under a needle-plate discharge model. PD optical pulses in transformer oil contained signal-peak and multi-peak pulse waveforms. Compared with UHF detection results, the number of PD pulses and the elapsed PD pulse phase time revealed a good corresponding relationship. However, PD signal amplitudes presented the opposite, thus indicating that PD UHF signals reflected pulse amplitude value, whereas PD optical signals reflected pulse energy magnitude. The n-u-φ three-dimensional distributions indicated that most of the PD signals concentrated in the nearby industrial frequency voltage peak value. Overall, the proposed fluorescent fiber sensing system design can be used successfully in transformer PD signal detection.